'Pure Feelings, Noble Aspirations and Generous Ideas': The Martí–Dana Friendship and the Cuban War of Independence1. (December 2016) - Collins, Michael
Abstract : This article considers the friendship between the Cuban leader José Martí and the US journalist Charles Anderson Dana in relation to questions of transnationalism, print culture, modernist aesthetics, and the politics of dissent during the era of the Cuban War of Independence (1895–8). It investigates the radical potential and aesthetic difficulties of rendering genuine affection in print at a time in which American friendliness towards Cuba often served to mask imperialist intentions. I offer a reading of Charles Dana's obituary for José Martí as a text that destabilizes assumptions about Cuban–American relations in the late nineteenth century by presenting an alternative political vision that incorporated the possibility of an autonomous Cuban subjectivity. In doing this, I resurrect the work of Charles Dana as a proto-modernist alternative vision of US culture that deployed the history of American Transcendentalism within the forms of late-nineteenth-century print media to register his opposition to the rise of modern press magnates such as W.R. Hearst and Joseph Pulitzer. This article challenges dominant narratives on two fronts: first, by suggesting an alternative to normative accounts of the development of the late-nineteenth-century commercial press; second, by exploring the mutual interpenetration of Latin American and US American radical history.